2000
DOI: 10.1021/jf9904620
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Primary Steps of Degradation of Carotenoids by Acid in Homogeneous Solution

Abstract: The kinetics of reaction between trifluoroacetic acid as an acid of medium strength and the carotenoids beta-carotene, zeaxanthin, canthaxanthin, and astaxanthin has been examined in detail including the effects of dioxygen, acid concentration, and carotenoid structure. Reaction between acid and carotenoid leads to species absorbing in the red and near-infrared (NIR) spectral regions, intermediates that subsequently disappear. ESR experiments clearly show that these species are not carotenoid radicals, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 30 publications
5
55
0
1
Order By: Relevance
“…Antioxidant supplementation of feed is an efficient method for increasing poultry meat oxidative stability [74]. Moreover, β-carotene, a pro-vitamin A compound abundant in forages, is the predominant carotenoid in meat and meat products [75]. Feeding of dehydrated leguminous-based forage vitamin E homologs and β-carotene for broiler meat oxidative stability remains, however, to be established [73].…”
Section: Influence Of Feeding Forage On Poultry Egg and Meat Qualitymentioning
confidence: 99%
“…Antioxidant supplementation of feed is an efficient method for increasing poultry meat oxidative stability [74]. Moreover, β-carotene, a pro-vitamin A compound abundant in forages, is the predominant carotenoid in meat and meat products [75]. Feeding of dehydrated leguminous-based forage vitamin E homologs and β-carotene for broiler meat oxidative stability remains, however, to be established [73].…”
Section: Influence Of Feeding Forage On Poultry Egg and Meat Qualitymentioning
confidence: 99%
“…Mortensen et al studied degradation of carotenoids with nitric acid and moderately strong acids, such as trichloroacetic and trifluoroacetic acids [72]. The intermediary reactions were mono-and di-protonated carotenoids, which exhibited a long lifetime (hours) in the experimental conditions of the study.…”
Section: Effect Of Food Compositionmentioning
confidence: 99%
“…The fraction of cis isomers present in our diet 303 is usually produced by technological treatments, in particular elevated temperatures 304 (Milanowska & Gruszecki, 2005;Rodriguez-Amaya, 1999;Updike & Schwartz, 2003). A 305 "trans to cis" conversion in the acidic environment of the stomach has also been proposed 306 (Mortensen & Skibsted, 2000), although it has not been observed in vivo (Richelle, et al, 307 2010;Tyssandier, et al, 2003). However, Richelle et al reported lycopene conversion to 308 occur within the enterocyte (Richelle, et al, 2010).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%